2014
DOI: 10.1016/j.nbd.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and electrophysiological changes in intratelencephalic-type pyramidal neurons in the motor cortex of a rat model of levodopa-induced dyskinesia

Abstract: Levodopa-induced dyskinesia (LID) is a major complication of long-term dopamine replacement therapy for Parkinson's disease, and becomes increasingly problematic in the advanced stage of the disease. Although the cause of LID still remains unclear, there is accumulating evidence from animal experiments that it results from maladaptive plasticity, resulting in supersensitive excitatory transmission at corticostriatal synapses. Recent work using transcranial magnetic stimulation suggests that the motor cortex di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…In addition, accumulating evidence indicates a role for other brain regions. This includes the cortex, with LIDs correlating with supersensitive excitatory transmission at corticostriatal synapses (Ueno et al, 2014) and high-frequency cortical oscillations (Richter et al, 2013). The cerebellum also plays a role in LIDs possibly via the primary motor cortex (Kishore and Popa, 2014; Kishore et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accumulating evidence indicates a role for other brain regions. This includes the cortex, with LIDs correlating with supersensitive excitatory transmission at corticostriatal synapses (Ueno et al, 2014) and high-frequency cortical oscillations (Richter et al, 2013). The cerebellum also plays a role in LIDs possibly via the primary motor cortex (Kishore and Popa, 2014; Kishore et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Severe loss of nigral dopaminergic neurons, leading to a dramatic striatal dopamine depletion, is an essential precondition for the expression of LID 8,9 . However, hyperkinesias only occur if associated with subtle alterations of the dendritic spines of cortical and striatal neurons 10,11 .…”
mentioning
confidence: 99%
“…It has been reported that dSPNs appear to play an important role in the development of LID (Picconi et al, 2003; Shen et al, 2015). In a previous study, we found enlargement of IT neuron spines in a LID model rat and proposed that IT neurons in the M1 may store abnormal information resulting in LID (Ueno et al, 2014). Furthermore, IT neurons in the M1 of the LID rat model displayed increased amplitudes of miniature excitatory postsynaptic currents (Ueno et al, 2014).…”
Section: Introductionmentioning
confidence: 82%